What Is and Isn’t an Ectodermal Dysplasia? - Peschel, Nicolai; Schneider, Holm (Springer Nature, 2025)
This chapter discusses the classification of ectodermal dysplasias, which has evolved over decades from one based purely on clinical symptoms to one based on molecular changes and signaling pathways. As there are many different disease entities and a broad spectrum of clinical manifestations, a distinctive classification according to the molecular pathways or the cell structures involved is not only useful but has become the gold standard for classifying any group of rare genetic diseases. The general transition from a descriptive clinical to a molecular approach occurred because user-friendly and accessible molecular diagnostic tests are now available in almost every diagnostic laboratory and because the identification of pathogenic gene variants can often quickly objectify a clinical suspicion, allowing better comparability of the different patients seen by healthcare professionals.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Classification; Criteria; Syndromes